2009
DOI: 10.2135/cropsci2008.05.0247
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Vigor, and Proteome of Mature Soybean Seeds Developed under High Temperature

Abstract: The effects of high temperature treatment on soybean [Glycine max (L.) Merr.] seed composition, vigor, and proteome were investigated using mature dry seeds harvested from plants grown in environment‐controlled chambers. High day/night temperatures (37/30°C) from stages R5 through R8 altered ratios of individual fatty acids to total fatty acid compared to the control (27/18°C). Concentration of sugars decreased, but total protein and phytic acid concentration were unchanged. High temperature resulted in a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 75 publications
6
80
0
4
Order By: Relevance
“…From the time when these initial publications appeared, the study of heat-induced HSPs has been continuous, aiming to identify particular molecular species. The most recent investigations have made use of the proteomic technology; most HSPs have been identified as stabilizing (refolding) proteins, storage proteins or respiratory-related proteins (Ren et al, 2009). Although HSPs are meant to prevent, and even reverse, the molecular alterations induced by heat (Boston et al, 1996), they might be inefficient in cell protection when the temperature intensity is beyond the tolerance threshold (Schöffl et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…From the time when these initial publications appeared, the study of heat-induced HSPs has been continuous, aiming to identify particular molecular species. The most recent investigations have made use of the proteomic technology; most HSPs have been identified as stabilizing (refolding) proteins, storage proteins or respiratory-related proteins (Ren et al, 2009). Although HSPs are meant to prevent, and even reverse, the molecular alterations induced by heat (Boston et al, 1996), they might be inefficient in cell protection when the temperature intensity is beyond the tolerance threshold (Schöffl et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that raffinose and galactinol levels may play an important role in plant tolerance to biotic and abiotic stress [14,15], and the accumulation of galactinol and raffinose may protect the plant from drought [51], and the activity of sucrose synthase, the main enzyme involved in sucrose hydrolysis in nodules, was significantly inhibited under drought conditions [52,53]. The biological functions of raffinose and stachyose are not clear [54], but previous research reported that oligosaccharides (sucrose, raffinose, and stachyose) are related to seed quality [55] and the acquisition of desiccation tolerance during seed development and maturation.…”
Section: Effects Of B and Water Stress On Seed Sugarsmentioning
confidence: 99%
“…Exposure of soybean plant to a temperature of 35 °C for 10 hours per day resulted in about a 27% reduction in yield (Gibson & Mullen, 1996). High temperatures during seed development changed the seed components, in which concentrations of palmitic, stearic, and oleic acids increased, whereas those of linoleic and linolenic acids decreased; there was also a marked decrease in seed vigor (Ren et al, 2009). One of the main deleterious effects of high temperatures during soybean growth is the disruption of photosynthesis, and it has been reported that, among the various components of the photosynthetic apparatus, photosystem II (PS II) is particularly sensitive to high temperatures (Thompson et al, 1989).…”
Section: High Temperaturementioning
confidence: 99%
“…Only few proteomics studies have been performed on soybean subjected to hightemperature stress. In one of the experiments, total proteins have been extracted from mature seeds of soybean plants grown under normal and high temperatures in growth chambers (Ren et al, 2009), and 20 heat stress-responsive proteins were identified by using the 2D-DIGE technique. The accumulation of heat shock protein 22 (HSP 22) was shown to increase in seeds that developed at a high temperature.…”
Section: High Temperaturementioning
confidence: 99%
See 1 more Smart Citation